Military Dentistry: Terrain, Trends and Training - Singh Paramjit, Arora Vimal; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2005)
The book provides a comprehensive insight about military dentistry in the national and international perspective. The book has been divided into two parts$1 (Bthe International and the Indian. The International section deals with the Dental Services of various countries including that of India and has been arranged in an alphabetical manner. The Dental Services of Indian Army, Navy and Air Force, however have been presented in the beginning as the book basically delves mainly into the realms of Indian scenario. The National section deals with relevant topics under various heads like Organisation and personnel, Delivery of Dental services, Modalities of specialised care, Research and development, Veteran care and Infection control protocol. The Delivery of Dental Services deals with the norms of dental care as applicable to Indian Dental Services and the modalities of providing the same. Specialised care to all combatants in war and peace has been covered extensively under the Modalities of Specialised care. A new beginning by the Armed forces by starting Ex-service Man Contributory Health Scheme has been covered under Veteran Care along with Resettlement, though strictly speaking, resettlement is not within the domain of the Army Dental Corps. Giving due consideration to the present day scenario of asepsis and surgical protocol, special chapters on Infection Control and Waste Management have been added.s
Keywords: General Dentistry; Electronic books